Concreto colorido a partir de ecocimento LC3 - EVANGELISTA, Erika Lima (2023)
The contemporary architecture scenario demonstrates the search for innovative materials that meet the demands of durability, load, economy, beauty and sustainability. In this context, architects explore the use of chromatic concrete, so that a structural element also becomes an aesthetic element. Chromatic concrete can be produced with white Portland cement or conventional Portland cement, but white Portland cement has a higher cost and conventional Portland cement has reduced pigment capacity. A more viable alternative for chromatic concrete production would be the use of LC³ (Limestone Calcined Clay Cement), a material that partially replaces cement with mineral additions such as limestone and metakaolin. In addition to its lower cost compared to white Portland cement, LC³ can also offer greater pigment capacity than conventional Portland cement. Another benefit of LC³ is the reduction of carbon dioxide release due to the lower amount of clinker in its composition. In this sense, the present research aimed to comparatively evaluate the colorimetric performance of LC³ in relation to conventional Portland cement. The results obtained in this research were very satisfactory, since the achieved parameters demonstrated that the total color difference between the LC³ and conventional Portland cement (CPIIF40) plates is quite sharp, being easily noticed in a simple visual evaluation. LC³ was also effective in combating efflorescence, reducing the surface porosity of the plates. Variations between textures (smooth, slatted and bamboo) were also analyzed, indicating that rougher surfaces tend to darken the color of the material.